2010
DOI: 10.1590/s0104-66322010000200014
|View full text |Cite
|
Sign up to set email alerts
|

Application of biowaste (waste generated in biodiesel plant) as an adsorbent for the removal of hazardous bye - methylene blue - from aqueous phase

Abstract: -Solid waste (SW) from a biodiesel plant has been successfully used for the removal of the hazardous cationic water soluble dye -methylene blue (MB) -from an aqueous phase. Batch adsorption studies were carried out by monitoring the pH, amount of adsorbent, initial dye concentration and contact time. Attempts have also been made to monitor the adsorption process through Langmuir, Freundlich, Temkin and D-R adsorption isotherm models. Relevant thermodynamic parameters were calculated and it was found that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
(27 reference statements)
3
16
0
Order By: Relevance
“…3(a)) showed an intense absorption band at 3280 cm À1 , which is relative to the -OH groups on the FPSP surface [12]. The bands at 2920 and 2857 cm À1 can be assigned to the stretching of OH groups bound to the methyl group (C-OH) [8,34,35]. The band observed at 1740 cm À1 is relative to the carbonyl group (C5 5O) of carboxylic acid or ester [12].…”
Section: Characterization Of the Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a)) showed an intense absorption band at 3280 cm À1 , which is relative to the -OH groups on the FPSP surface [12]. The bands at 2920 and 2857 cm À1 can be assigned to the stretching of OH groups bound to the methyl group (C-OH) [8,34,35]. The band observed at 1740 cm À1 is relative to the carbonyl group (C5 5O) of carboxylic acid or ester [12].…”
Section: Characterization Of the Adsorbentmentioning
confidence: 99%
“…Thus, it is necessary to remove such contaminants from the industrial effluents, in order to protect the environment and offer people a better quality of live. In this way, several scientific studies have shown that popular processes such as electrochemical [4], biological [5], liquid-liquid extraction [6], oxidation [7] and adsorption [8] can be used with success for the removal of different classes of dyes from aqueous phase. Among these, adsorption has been extensively employed for the removal of dye molecules from different types of water due to its easy operational conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…The samples were sputter-coated with a thin conductive layer of gold for 400 s, and images were then obtained using an acceleration voltage of 10 kV with magnification ranging from 300 to 2000 fold. The thermal profile of the S. platensis particles was obtained in a N 2 atmosphere using TG and DTG curves (PG instruments, SDT Q600, U.K.) (Gottipati and Mishra, 2010).…”
Section: Preparation and Characterization Of Spirulina Platensismentioning
confidence: 99%
“…Langmuir, Freundlich, Redlich-Peterson, Temkin, Dubinin-Radushkevich, etc., that can be used for biomolecules, e.g. chitosan (Gottipati and Mishra, 2010;Kumar et al, 2010;Piccin et al, 2011), but the Sips model proved to be the best for vancomycin adsorption onto polymeric resin (Likozar et al, 2012).…”
Section: Theory and Calculationmentioning
confidence: 99%